53rd Electronic Components and Technology Conference, 2003. Proceedings.
DOI: 10.1109/ectc.2003.1216313
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modeling and design of liquid cooled heat sinks assembled vvith flip chip ball grid array packages

Abstract: Development of advanced cooling techniques is required for electronic packages with high power dissipation such as microprocessors. In this paper, a liquid cooling setup is proposed and the thermal modeling and design of a liquid cooled microchannel heat sink assembled with a flip chip ball grid array (FCBGA) package are addressed, with an emphasis on the removal of a heat flux beyond 100W/cm2. A full model, which includes the microchannel heat sink with inletloutlet manifolds, the package and thermal test hoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The adoption of vapor chamber heat sink (VCHS) significantly reduces the spreading thermal resistances at the heat sink base and, correspondlyg, facilitates the use of large heat sinks [7-81. Another altemative and promising way to handle the large amount of power dissipation is to use liquid cooled heat sinks (LCHS) with microchannel structure. Studies on the liquid-cooled microchannel heat sinks only can he found in literature, for instance, [4, [9][10][11], This indirect liquid cooling technology can be used when the power dissipation exceeds the air cooling limit, with the least modification in the electronic system compared with other high flux thermal management techniques such as direct liquid cooling and refrigeration cooling. However, the study of the microcha~lel heat sink assembled on the electronic packages, which aims at immediate assessment of the chip to the ambient thermal performance and the cooling loop behavior, has not been well addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of vapor chamber heat sink (VCHS) significantly reduces the spreading thermal resistances at the heat sink base and, correspondlyg, facilitates the use of large heat sinks [7-81. Another altemative and promising way to handle the large amount of power dissipation is to use liquid cooled heat sinks (LCHS) with microchannel structure. Studies on the liquid-cooled microchannel heat sinks only can he found in literature, for instance, [4, [9][10][11], This indirect liquid cooling technology can be used when the power dissipation exceeds the air cooling limit, with the least modification in the electronic system compared with other high flux thermal management techniques such as direct liquid cooling and refrigeration cooling. However, the study of the microcha~lel heat sink assembled on the electronic packages, which aims at immediate assessment of the chip to the ambient thermal performance and the cooling loop behavior, has not been well addressed.…”
Section: Introductionmentioning
confidence: 99%